Pengaruh Ukuran Perusahaan, Leverage dan Sales Growth Terhadap Manajemen Laba - Dian Sadewa; Dani Sopian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to determine the influence of company size, leverage, and sales growth on earnings management. The population in this study consists of all companies in the healthcare sector in the Indonesia Stock Exchange during the period from 2018 to 2022. The population for this study consists of 33 companies. This research uses a sample of 14 companies over a 5-year period. The sampling was done using purposive sampling. This is a quantitative research that employs classic assumption tests and multiple linear regression analysis. The results of this research simultaneously (F-test) show that 3.145 > 0.219 with a significance value of 0.996. A significance value of 0.883 > 0.05 means that the variables of company size, leverage, and sales growth collectively do not significantly influence earnings management.